Our Daily Bread Is At Risk: The Term rōzīq/g as Vorlage for ἐπιούσιος in Lord’s Prayer - Shapira, Dan (Verbum Vitae, 2022)
This note proposes a new hypothesis that ἐπιούσιος of the Lord's Prayer in Matthew 6:11 and Luke 11:3 was an attempt to translate adequately rōzīq/g, the Middle Iranian loan word in Jesus' Hebrew / Aramaic, whose meaning was ‘nourishment provided by God's mercy day to day’, and not merely ‘daily [bread], needed for the day/for today’.